Tissue resident CD8 T cells subsets: prognostic significance in colorectal cancer - Talhouni, Shahd (2022)
The past few years have seen remarkable success in the field of oncology with the advent of cancer immunotherapies and checkpoint inhibitors. The effectiveness of immunomodulatory strategies has been shown to depend on natural intra-tumoral T cell infiltration and on reactivation of pre-existing immunity via inhibition of inhibitory checkpoints on T cells. T-cell membrane microdomains are enriched with proteins and glycolipids collectively involved in cell activation and signal transduction. Tetraspanin-enriched microdomains are an example of such microdomains that have been shown to play a pivotal role in T-cell regulation. One such tetraspanin protein is TSPAN32 that has not been widely studied. For the purpose of further studying the immuno-regulatory role of TSPAN32, especially in its ability to inhibit T cell proliferation, we developed an innovative immunisation method using plasma membrane glycolipid extraction of TSPAN32 transfected cells to produce an anti-TSPAN32 antibody. Developing a fully function TSPAN32 monoclonal antibody could help further understand its immune function and could also potentially help in the development of novel immunotherapies that improve immune response in cancers.